Micro-poetical innovations in novels of L.-P. Selin (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article deals with the most important authorial innovations at the level of micro-poetics of the novel "Journey to the End of the Night" by Louis-Ferdinand Сeline, in particular lexical and syntactic. The results of the study give an opportunity to make a number of conclusions about the formation of a fundamentally new type of artistic whole in the novel.
Keywords: micro-poetics; L.-F. Celine; poetics; novel